School Literacy Movement in Penujak Village, Central Lombok Regency (Community Service) - Mohamad Mustari; Sudirman Wilian; Heri Hadi Saputra; Syarifuddin; Fahruddin (Pascasarjana Universitas Mataram, 2025)
The School Literacy Movement in Penujak Village, Central Lombok Regency, is discussed in this article. The goal is to increase children's literacy and reading interest in seven Elementary Education Schools (SD) in the Penujak Village Cluster, the target of this socialization is Principal and Teachers, as well as village libraries in the community are all involved in creating a sustainable literacy culture through a participatory approach and collaboration of this activity. This service was carried out with a work shop model socializing the school Literacy Movement with resource persons from lecturers, practitioners and village library managers. The basis for this community service is to see the achievement of literacy and numeracy indicators on the last two years of education report cards which show that several schools have experienced a decrease in achievement. These findings show that the implementation of literacy and numeracy programs needs to increase the involvement of the community and parents as well as village libraries in education while improving students' reading skills. The obstacles that must be overcome include problems such as lack of resources and infrastructure as well as collaboration between stakeholders. To strengthen the literacy and numeracy movement in hamlets, this article suggests that additional assistance with facilities and infrastructure is needed from the government, village libraries, and other non-governmental organizations.